The POGIL Model Integrated Flipped Classroom Assisted Learning Management System (LMS) for Learning Solution in ERI 4.0 - Suci Sukmawati Syafei; Mawardi Mawardi (Postgraduate, University of Mataram, 2022)
The use of technology in learning is highly demanded during the covid-19 pandemic and the development period of the Industrial Revolution Era 4.0. The right learning model is a challenge that must be solved by educators. The LMS-assisted FGIL model was introduced as an appropriate model used for current and future learning. This development is a type of EDR (Educational Design Research) research with a plomp research model. Lecturers as expert review, and 12 students became the subject of research in this development research. The data obtained in the form of content validity data and media validity was processed using Aiken's V formula, while practicality data was processed with practical percent. Based on the results of the study obtained a value of V for content validity and media validity of 0.88; and 0.91; which is in the valid category. Then the practical results showed a value of 89.00% with a very practical category. So, it can be concluded that the model developed has been valid and practical so that it is worth using in learning